El futuro oscuro latinoamericano en Angelus Hostis y Policía del Karma (Crítica) - Londoño Proaño, Cristián Fernando (2026)
Many works of science fiction in literature, theater, film, comics, television, and video games envision different futures for Latin America, connected to social and political realities and the particularities of each subregion. However, some creations share common points and questions. This study aims to analyze and compare two graphic novels: Angelus Hostis (2012), by Ecuadorian writer Santiago Páez (story) and Rafael Carrasco (art), and Policía del Karma (2011), by Chilean writer Jorge Baradit (story and graphics) and Martín Cáceres (art). Both works are science fiction within the cyberpunk subgenre and are heavily influenced by police narratives. Angelus Hostis is an intense, dark, and moving story, shaped by myths, religious synchronicity, and technology. In contrast, Policía del Karma is a dark and harrowing tale that exposes the violence of Latin American dictatorships and incorporates elements such as religious syncretism, militarism, and shamanism. The works differ significantly due to the social realities and specific contexts of each subregion: Angelus Hostis is set in Cuenca, Ecuador, while Policía del Karma takes place in Santiago, Chile. Despite these differences in setting, both works share insights about their vision of Latin America’s future and raise questions about human evolution in relation to technology, which could plausibly lead to the loss of humanity itself, perhaps even the erosion of fundamental emotions.